1987
DOI: 10.1002/1097-4679(198705)43:3<346::aid-jclp2270430308>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Normative data for the Halstead-Reitan neuropsychological tests stratified by age and sex

Abstract: Normative data, stratified by age and sex, are presented for the Halstead‐Reitan neuropsychological tests: Name Writing, Speech‐Sounds Perception, Trail Making, Halstead Category, Finger Tapping, Dynamometer, Tactual Performance, Seashore Rhythm, Tactile Form Recognition, Finger‐Tip Number Writing Perception, Face‐Hand, and Finger Localization. Correlations of the test variables with age, education, and WAIS‐R Verbal and Performance IQ are reported. The normative sample consisted of 225 adults (127 males, 98 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
1
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 16 publications
8
55
1
1
Order By: Relevance
“…It is consistent, however, with previous research that questions the nonverbal properties of the Category Test (Lin & Rennick, 1974;Shore et al, 1971;Seidenberg, Giordani, Berent, & Boll, 1983;Yeudall et al, 1987). Several explanations may account for this discrepancy: First, both the BCT and CV-CAT utilized verbal feedback ("correct," "incorrect") in administration, as opposed to the simple auditory feedback ("doorbell,"…”
Section: Chapter IV Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is consistent, however, with previous research that questions the nonverbal properties of the Category Test (Lin & Rennick, 1974;Shore et al, 1971;Seidenberg, Giordani, Berent, & Boll, 1983;Yeudall et al, 1987). Several explanations may account for this discrepancy: First, both the BCT and CV-CAT utilized verbal feedback ("correct," "incorrect") in administration, as opposed to the simple auditory feedback ("doorbell,"…”
Section: Chapter IV Discussioncontrasting
confidence: 99%
“…Finally, Vanderploeg and Logan (1989) criticized the linear extrapolation established by Russell and Levy (1987) These results were consistent with Cullum et al (1984), Lansdell and Donnelly (1979), and Swiercinsky (1979) who noted similar relationships between the CAT-208 and the WAIS/WAIS-R Performance and Verbal Scale IQs. However, the results contrast the reports of Lin and Rennick (1979), Shore et al (1971), and Yeudall et al (1987) who reported opposite relationships between the CAT-208 and the WAIS/WAIS-R Performance and Verbal Scale IQs. In contrast to Tupper (1990) and Cullum et al (1984), however, Corrigan et al (1987 noted that the CAT-208 and the WAIS-R Performance subtests captured different phenomena.…”
Section: Labreche (1983) Dropped Subtests 1 and 7 In The Victoriamentioning
confidence: 99%
“…Scores range from 0 to 100, and lower scores indicate poorer cognitive function. The Trailmaking B (Trails B) test is a timed test of executive function, a cognitive domain not assessed with the 3MS (21). Higher scores on the Trails B indicate poorer executive function.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…In addition to the CAT-208, the Tactile Performance Test and the Performance Scale of the WAIS loaded on this factor. Yeudall, Reddon, Gill, and Stefanyk (1987), in a sample of 225 normal adults, reported few substantial correlations between the HRNB and the WAIS-R. The CAT-208 did correlate significantly and negatively with the Verbal Scale IQ (r, = -.34) and the Performance Scale IQ (r. = -.29).…”
Section: Localization Of Function By the Category Testmentioning
confidence: 52%
“…Other than the warning by Ryan et al (1983) about the discrepancy between WAIS and WAIS-R scores, little research has examined the relationship of the CAT-208 to the Wechsler Adult Intelligence Scale -Revised (Davidoff et al, 1985;Roth et al, 1989;Yeudall et al, 1987). Only Corrigan et al (1987) Based on a review of the literature, the following hypothesis appears warranted:…”
Section: Automation and The Category Testmentioning
confidence: 99%